Expansion of the Concept of Nonlinear Effects in Catalytic Reactions Beyond Asymmetric Catalysis. Issue 16 (2nd March 2016) - Pollice, Robert; Schnürch, Michael
Abstract: The observation and investigation of nonlinear effects in catalytic reactions provides valuable mechanistic insight. However, the applicability of this method was, until now, limited to molecules possessing chirality and therefore to asymmetric synthesis. The concept of nonlinear effects is expanded to catalytic reactions beyond asymmetric catalysis by using derivatives instead of enantiomers and by considering rates instead of enantiomeric excess. Additionally, its systematic application to investigate the mechanism of catalytic reactions is presented. By exceeding the limitation to asymmetric reactions, the study of nonlinear effects can become a general tool to elucidate reaction mechanisms. Abstract : Escaping asymmetry : The concept of nonlinear effects is expanded from asymmetric catalysis to catalytic reactions in general by investigating reaction rates instead of enantiomeric purity and using derivatives instead of enantiomers.